Efficacy of milk powder additive in biocementation technique for soil stabilization - Jie Yin; Lexuan Zhang; Ke Zhang; Cheng Zhang; Yang Yang; Mohamed A. Shahin; Liang Cheng (Biogeotechnics)
Microbial-Induced Carbonate Precipitation (MICP) is an emerging, environmental-friendly, and sustainable technology that has shown great potential for soil stabilization. However, its process efficiency has been recognized as a major challenge for its practical application in engineering. Non-fat powdered milk (NFPM) has been shown to have positive effects in enzymatical-induced carbonate precipitation (EICP), so in this study, we evaluated its use as an additive in the MICP process. A comparison between conventional MICP and NFPM-modified MICP was conducted, including chemical conversion efficiency, urea hydrolysis rate, and mechanical performance of sandy soils. A series of laboratory tests including precipitation analysis, unconfined compressive strength (UCS), and microstructure analysis were conducted. The results showed that the addition of NFPM could improve urease activity, enhance chemical conversion efficiency, and lead to superior strength improvement compared to conventional MICP. Microstructure and particle size analysis revealed that the presence of NFPM was beneficial for larger crystal cluster formation between sand grains, which could result in stronger bonds and better mechanical performance. In summary, this study indicates that the use of NFPM in MICP process can represent a more sustainable and economically viable approach for soil stabilization. The findings provide valuable information for engineers and researchers working in soil stabilization and environmental engineering, highlighting the potential of using natural additives such as NFPM to promote the sustainable development of MICP technique.